Overview Quality of Life Diabetes Mellitus of Tipe II Patients - Nurani, Rahmawati Dian; Pitora, Tobi; Bunga, Dinda Nur Fajri Hidayati; Khoirot, Risyda Ma’rifatul (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Diabetes mellitus (DM) is a global health threat, both in Indonesia and globally. Nearly half a billion people live with diabetes. DM patients experience elevated blood sugar levels (hyperglycemia) caused by abnormalities in insulin secretion, insulin action, or both. The purpose of this study was to determine the quality of life in patients with Type II Diabetes Mellitus. A quantitative descriptive method was used with 70 respondents with diabetes mellitus selected by accidental sampling. The research instrument used was the DQOOL questionnaire. Data collection was conducted in August 2024. The results of the study from 70 respondents showed that the most dominant respondents were type II DM patients with a good quality of life of 38 people (54.3%), and a poor quality of life of 32 people (45.7%). The conclusion of this study is that the majority Diabetes Mellitus of Type 2 Patients at Abdul Moeloek Hospital are elderly people with hypertension. These findings are expected to motivate Type 2 Diabetes Mellitus patients to improve their quality of life.